Bacterial volatile organic compounds (VOCs) promote growth and induce metabolic changes in rice - Almeida, Octávio Augusto Costa; de Araujo, Natália Oliveira; Mulato, Aline Tieppo Nogueira; Persinoti, Gabriela Felix; Sforça, Maurício Luís; Calderan-Rodrigues, Maria Juliana; Oliveira, Juliana Velasco de Castro (Frontiers in Plant Science, 2023)
Plant growth promoting bacteria (PGPB) represent an eco-friendly alternative to reduce the use of chemical products while increasing the productivity of economically important crops. The emission of small gaseous signaling molecules from PGPB named volatile organic compounds (VOCs) has emerged as a promising biotechnological tool to promote biomass accumulation in model plants (especially Arabidopsis thaliana) and a few crops, such as tomato, lettuce, and cucumber. Rice (Oryza sativa) is the most essential food crop for more than half of the world’s population. However, the use of VOCs to improve this crop performance has not yet been investigated. Here, we evaluated the composition and effects of bacterial VOCs on the growth and metabolism of rice. First, we selected bacterial isolates (IAT P4F9 and E.1b) that increased rice dry shoot biomass by up to 83% in co-cultivation assays performed with different durations of time (seven and 12 days). Metabolic profiles of the plants co-cultivated with these isolates and controls (without bacteria and non-promoter bacteria - 1003-S-C1) were investigated via 1H Nuclear Magnetic Resonance. The analysis identified metabolites (e.g., amino acids, sugars, and others) with differential abundance between treatments that might play a role in metabolic pathways, such as protein synthesis, signaling, photosynthesis, energy metabolism, and nitrogen assimilation, involved in rice growth promotion. Interestingly, VOCs from IAT P4F9 displayed a more consistent promotion activity, and were also able to increase rice dry shoot biomass in vivo. Molecular identification by sequencing the 16S rRNA gene of the isolates IAT P4F9 and E.1b showed a higher identity with Serratia and Achromobacter species, respectively. Lastly, volatilomes of these and other two non-promoter bacteria (1003-S-C1 and Escherichia coli DH5α) were evaluated through headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry. Compounds belonging to different chemical classes, such as benzenoids, ketones, alcohols, sulfide, alkanes, and pyrazines, were identified. One of these VOCs, nonan-2-one, was validated in vitro as a bioactive compound capable of promoting rice growth. Although further analyses are necessary to properly elucidate the molecular mechanisms, our results suggest that these two bacterial isolates are potential candidates as sources for bioproducts, contributing to a more sustainable agriculture.